Certolizumab pegol – A new therapeutic option for refractory disseminated pyoderma gangrenosum associated with Crohn's disease. (2nd January 2016) - Hurabielle, Charlotte; Schneider, Pierre; Baudry, Clotilde; Bagot, Martine; Allez, Matthieu; Viguier, Manuelle
Abstract: Systemic steroids, in association or not with cyclosporin, are indicated for the treatment of large or widespread Pyoderma gangrenosum (PG). We report the case of a 27-year-old woman with a 15-year history of severe Crohn's disease, who developed a severe and disseminated PG, refractory to multiple lines of treatment. Infliximab and adalimumab were contraindicated, either because of allergy or of ineffectiveness on Crohn's disease. The addition of certolizumab pegol to the baseline treatment, associating systemic steroids and tacrolimus, finally allowed the complete healing of PG. Oral prednisone was stopped and tacrolimus was decreased, without any cutaneous or digestive relapse. Certolizumab pegol could be an alternative therapy in the treatment of PG in case of intolerance or ineffectiveness of the other anti-tumor necrosis factor (anti-TNF) therapies.